EFEKTIVITAS EDUKASI KESEHATAN DENGAN BUKU KIA DAN MEDIA ELEKTRONIK TERHADAP DETEKSI DINI KEHAMILAN RISIKO TINGGI PADA IBU HAMIL - Siti Najmah; Suryani Suryani; Imelda Imelda (NHM PRESS, 2022)
High-risk pregnancies are pregnancies that can have an impact on pregnant women and babies becoming sick and even dying before birth occurs. The purpose of this study was to determine the effect of education using MCH books and electronic media on the knowledge of pregnant women about high risk detection in pregnant women in the Simpang Tuan Health Center work area in 2022. This study used a quasi-experimental method with a one group pre test post test design. . The population in this study were all pregnant women who were in the work area of ​​the Simpang Tuan Health Center in 2022 as many as 125 people. The number of samples as many as 50 people who were divided into 2 groups were taken by simple random sampling technique, statistical analysis test using the Wilcoxon test. Based on the results of the study, it was found that there was a difference in knowledge of the MCH book and electronic media in counseling about high risk detection for pregnant women at the Simpang Tuan Health Center in 2022. The mean value of the MCH book review was higher than the electronic media. Statistical results show p-value 0.000 or p<0.05. The use of MCH handbooks as an educational medium for pregnant women to increase knowledge about high-risk pregnancy detection.